Effect of aging and sex on cardiovascular structure and function in wildtype mice assessed with echocardiography - Tian Yu Zhang (Nature Portfolio, 2021)
Abstract This study employed traditional and advanced echocardiographic techniques to assess comprehensively age- and sex-related changes in cardiovascular structure and function in wildtype (WT) mice. Forty-five normal adult wildtype mice were apportioned to groups based on age and sex: 2-month (young) male or female, and 24-month (old) male or female (n = 13, 13, 13, and 6, respectively). Each underwent 2-dimensional (2D) imaging echocardiography, Doppler, tissue Doppler imaging echocardiography, and speckle-tracking echocardiography (STE) for comparison of cardiovascular structure and function parameters. Compared to the young mice, the old had significantly higher body weight (BW), and lower diastolic and mean arterial pressure. The left ventricular (LV) end-diastolic and end-systolic volumes, and left ventricular mass, were significantly higher in the old mice. Within each sex, the cardiac diastolic and systolic function parameters were comparable between the young and old. Isovolumetric relaxation time (IVRT)/diastolic time interval (DT) and the maximum drop rate of pressure in LV (− dP/dtmax) were significantly lower in the old mice, while the LV relaxation time constant (Tau) was significantly higher. Spearman’s rank correlation showed a positive association between IVRT/DT and − dp/dtmax (male r = 0.663; female r = 0.639). Among the males, the maximum rise rate of pressure in LV (+ dp/dtmax), and systolic global longitudinal strains and rates (S-GLS, S-GLSR) were significantly different between the young and old. Spearman’s rank correlation showed positive association between S-GLS, S-GLSR and + dp/dtmax (r = 0.709 and r = 0.499). Regarding vascular structure, the ascending aorta systolic and diastolic diameters were significantly higher in the old mice compared with the young. The male mice had progressive, age-related aortic stiffness. Ageing in mice leads to changes in cardiovascular structure and cardiac diastolic function, but systolic function is relatively well preserved in females. Changes in cardiac function and arterial stiffness were more significant in males than females. Traditional ECG is better than STE for evaluating LV diastolic function; STE is better for LV systolic function.